TEACHERS’ PERCEPTIONS ON USING COMMUNICATIVE LANGUAGE TEACHING IN THE ENGLISH CLASS - Rimajon Sotlikova; Sugirin Sugirin (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2016)
This study aimed to describe the EFL teachers’ understanding and knowledge about CLT, their attitudes toward CLT and their difficulties and challenges in the implementation of CLT practices in the Indonesian context. This study first presents an overview of CLT approach, the definition and principles of CLT which is followed by a brief history of CLT, and a review of existing literature related to comunicative competence, as well as how it functions in CLT is presented. Then, this study examines the impact of ESP in CLT contexts. A qualitative method research design was used for this research. Participants for this study were 13 lecturers of English teaching in Engineering Faculty of YSU. The main modes of data collection consisted of questionnaire, semi-structured interviews and documentions. The data of this research was collected by: distributing questionnaire for all English lecturers which numbers are 13, who teach the English language in Engineering Faculty of YSU; conducting interviews with 5 of them (they were chosen based on their background major); collecting Engineering Faculty’s syllabus for English class, learning book, lesson plans and additional teaching book in ESP context which was used for teaching English due to the circumstances in the Engineering Faculty. The data of this research, questionnaire was analyzed by Normal Curve category analyze. And the qualitative data of this research was analyzed by data reduction, data displays and data verification. The results show that the respondents have good understanding and knowledge about CLT; they have positive attitudes toward CLT; however, they observe many difficulties and challenges in implementing CLT in their classrooms.